1 - Global and Local Hybridity in African Youth Language Practices - Erastus, Fridah Kanana; Hurst-Harosh, Ellen (Africa Development, 2020)
This article investigates and describes youth language practices in Africa in the era of globalisation. It opens up debate over the impacts of globalisation on youth linguistic identities in Africa. Further, it suggests some aspects of youth participation in linguistic change in Africa and provides some examples of how youth linguistic cultures are practised in everyday interactions. The authors show the intersection of cultures in everyday discourse and in youth language vocabulary, and the incorporation of global (popular) culture in African youth language practices through bricolage to achieve hybridity. The ways in which the global intersects with the local and how the youth in Africa recontextualise the global and create local traditions of youth culture and identity are discussed and exemplified. The article concludes by arguing that, while global brands impact on youth language and practices, they are interpreted and applied locally; youth culture in Africa is enriched by global symbols and cultural artefacts and figures, not impoverished by them; the global does not displace the local, but rather complements it. The youth in Africa, in their spaces, are therefore active creators and contributors towards linguistic and cultural change and through this change they are agents of Africa’s globalisation.